Building a Stable European Deposit Insurance Scheme. Issue 2 (9th August 2018) - Schoenmaker, Dirk
ABSTRACT: Deposit insurance, like any insurance scheme, raises moral hazard concerns. Such concerns arising from European deposit insurance can be alleviated through a country-specific component in the risk-based premium for deposit insurance and limits on sovereign bond exposures on bank balance sheets. This article, which forms part of the Euro Area Reform debate, argues, however, that proposals to maintain national compartments in a new European Deposit Insurance Scheme are self-defeating, as such compartments can be destabilizing in times of crisis.